Multiple-aspect analysis of semantic trajectories : first International Workshop, MASTER 2019, held in conjunction with ECML-PKDD 2019, Würzburg, Germany, September 16, 2019, Proceedings /: first International Workshop, MASTER 2019, held in conjunction with ECML-PKDD 2019, Würzburg, Germany, September 16, 2019, Proceedings. (2020) - Unknown
No abstract available